ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN HARGA BAWANG PUTIH DI INDONESIA SETELAH PENERAPAN TARIF EHP ACFTA - Rahayu, Kadek Ica; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study is to analyze the factors that influence the growth of garlic prices in Indonesia after the implementation of the EHP ACFTA tariff. This research was conducted in Indonesia with 16 years of observation in the period 2005-2020. The data used is secondary data with data collection methods, namely non-behavioral observation. This study uses descriptive analysis techniques and multiple linear regression analysis. The results showed that domestic production of garlic, import volume of garlic, and garlic prices in China had a simultaneous effect on the growth of garlic prices in Indonesia. Partially, domestic production and import volume have a significant negative effect on the growth of garlic prices in Indonesia. Meanwhile, the price in China has no significant positive effect on the growth of garlic prices in Indonesia. The implication of this research is that there is needs to reduce the volume imports and seek to develop domestic production in order to reduce dependence on imported garlic.  Keywords: Garlic; Price Growth; Domestic Production; Imports Volume; Prices in China